2020
DOI: 10.1007/s42399-020-00480-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Developing Diabetic Peripheral Neuropathy: a Meta-analysis

Abstract: To identify risk factors for the development of diabetic peripheral neuropathy, systematic searches of PubMed, Embase, Web-of-Science, Cochrane and Google scholar databases were performed to conduct a meta-analysis of prospective studies that quantified major risk factors for diabetic peripheral neuropathy. Two authors independently extracted data for a random-effects meta-analysis. The standardized mean difference (SMD) and 95% CI for continuous data, and an odds ratio (OR) and 95% CI for dichotomous data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
2
1
Order By: Relevance
“…The hazard of developing Diabetic neuropathy among type two diabetic patients with retinopathy was higher than in type two DM patients without diabetic retinopathy. This finding is consistent with the findings of studies conducted in Sri Lanka [21], Netherlands [39], Jordan [40], Singapore [41], and china [28]. The clinical stages of diabetic retinopathy, the ongoing disturbance of the neurovascular unit, and the loss of auto-regulation may all be to blame for this.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The hazard of developing Diabetic neuropathy among type two diabetic patients with retinopathy was higher than in type two DM patients without diabetic retinopathy. This finding is consistent with the findings of studies conducted in Sri Lanka [21], Netherlands [39], Jordan [40], Singapore [41], and china [28]. The clinical stages of diabetic retinopathy, the ongoing disturbance of the neurovascular unit, and the loss of auto-regulation may all be to blame for this.…”
Section: Discussionsupporting
confidence: 89%
“…previous studies conducted in Gamo Gofa, Ethiopia [26], Tanzania [21], Burkina Faso [44], and Netherland [39]. This might be due to inflammation, oxidative stress, activation of the immune system, thickening of the blood vessels which results reduce blood flow to the nerve, conduction slowing, and axonal atrophy [45].…”
Section: Plos Onementioning
confidence: 96%
“…Increasing HbA1c levels will further accelerate and exacerbate neuropathy complications. [15][16][17][18][19] Meanwhile, the relationship between body mass index and the severity of diabetic neuropathy in this study was found to have no significant relationship.…”
Section: Resultscontrasting
confidence: 60%
“…The neurological comorbidity status of patients is not used to classify DSPN yet, however, there might be an intrinsic neurological mechanism that links DSPN to other neurological illnesses. Finally, waist circumference is strongly correlated with BMI, which has been reported to be a risk factor for developing DSPN 29 . From a clinical perspective it is worth mentioning that only waist circumference represents a modifiable risk factor which emphasises the role of obesity prevention and treatment also in the context of DSPN.…”
Section: Discussionmentioning
confidence: 91%